Risk factors of serofast state in patients undergoing syphilis: a meta-analysis of 17 cohort studies - Zeng, Xin; Ouyang, Yuan; Wang, Haoyun; Liu, Linna; Chen, Jiaxin; Zhu, Chengbin; Huang, Hong; Lin, Jin; Niu, Yanan; Liao, Lan; Yang, Na; Xiao, Chunlan; et al. (Frontiers in Immunology, 2025)
ObjectiveThe serofast state in syphilis refers to a persistent serological status where patients maintain stable specific antibody titers despite receiving standardized anti-syphilitic therapy, whose underlying mechanisms remain incompletely elucidated. This study aims to systematically identify risk factors associated with the occurrence of syphilitic serofast state through comprehensive clinical data analysis.MethodWe performed a systematic literature search in PubMed and Embase databases for studies published up to February 20, 2025. A random-effects model was employed for meta-analysis, with effect estimates expressed as relative risk (RR) presented with 95% confidence intervals (CIs). Methodological evaluations including sensitivity analyses and publication bias assessment were conducted to assess result robustness.ResultsA total of 17 cohort studies involving 4,662 eligible participants were included in this meta-analysis. The pooled results demonstrated significant associations between serofast state and primary syphilis (RR = 0.65; 95% CI: 0.44-0.96), latent syphilis (RR = 2.14; 95% CI: 1.47-3.11), female gender (RR = 1.19; 95% CI: 1.01-1.41), HIV coinfection (RR = 1.40; 95% CI: 1.09-1.79), and lower rapid plasma reagin (RPR) titers (≤1:32) (RR = 1.47; 95% CI: 1.02-2.13). No statistically significant associations were observed for secondary syphilis (RR = 0.81; 95% CI: 0.59-1.12), age >40 years (RR = 1.41; 95% CI: 0.80-2.49), or benzathine penicillin treatment (RR = 0.99; 95% CI: 0.86-1.13). These findings were validated through leave-one-out sensitivity analysis.ConclusionFemale gender, HIV coinfection, primary syphilis, latent syphilis, and low rapid plasma reagin (RPR) titers (≤1:32) emerged as significant risk factors for serofast state development, requiring particular attention during therapeutic management to optimize syphilis treatment outcomes.